Development of Mathematics Learning Strategy Modules to Enhance Motivation and Higher-Order Thinking Skills for Students at UIN Syahada Padangsidimpuan - Rangkuti, Ahmad Nizar (TARBIYA: Journal of Education in Muslim Society, 2024)
AbstractThis study aimed to develop a mathematics learning strategy module to enhance students' motivation and higher-order thinking skills using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework within the Research and Development (R&D) paradigm. Conducted during the even semester of the 2022/2023 academic year, it involved fourth-semester students in the Mathematics Education Program at UIN Syahada Padangsidimpuan. Quantitative and qualitative data were collected through interviews, observations, questionnaires, tests, and expert validation. Instruments included a module validation sheet, a learning motivation questionnaire, and a higher-order thinking skills test. Data were analyzed using the Paired Samples Test. Results showed the module was well-implemented, with validation scores of 87.86% and 86.01%, categorized as "good." The module effectively improved students' motivation and higher-order thinking skills, with pretest and posttest scores of 52.38 and 79.19 (motivation) and 72.81 and 79.75 (higher-order thinking skills), both with significant improvements (sig. 0.000 < 0.05). This research recommends further implementation and development of the module using the ADDIE framework for enhancing mathematics learning strategies.AbstrakPenelitian ini bertujuan untuk mengembangkan modul strategi pembelajaran matematika guna meningkatkan motivasi dan keterampilan berpikir tingkat tinggi siswa menggunakan kerangka ADDIE (Analysis, Design, Development, Implementation, and Evaluation) dalam paradigma Penelitian dan Pengembangan (R&D). Penelitian dilakukan pada semester genap tahun akademik 2022/2023 dengan melibatkan mahasiswa semester empat Program Studi Pendidikan Matematika di UIN Syahada Padangsidimpuan. Data kuantitatif dan kualitatif dikumpulkan melalui wawancara, observasi, kuesioner, tes, dan validasi ahli. Instrumen yang digunakan termasuk lembar validasi modul, kuesioner motivasi belajar, dan tes keterampilan berpikir tingkat tinggi. Data dianalisis menggunakan Uji Sampel Berpasangan. Hasil penelitian menunjukkan bahwa modul diimplementasikan dengan baik, dengan skor validasi 87,86% dan 86,01% dalam kategori "baik". Modul ini efektif meningkatkan motivasi dan keterampilan berpikir tingkat tinggi siswa, dengan skor pretest dan posttest masing-masing 52,38 dan 79,19 (motivasi) serta 72,81 dan 79,75 (keterampilan berpikir tingkat tinggi), keduanya menunjukkan peningkatan signifikan (sig. 0.000 < 0.05). Penelitian ini merekomendasikan implementasi lebih lanjut dan pengembangan modul menggunakan kerangka ADDIE untuk meningkatkan strategi pembelajaran matematika.  How to Cite: Rangkuti, A.N. (2024). Development of Mathematics Learning Strategy Modules to Enhance Motivation and Higher-Order Thinking Skills for Students at UIN Syahada Padangsidimpuan. TARBIYA: Journal of Education in Muslim Society, 11(1), 13-26. doi:10.15408/tjems.v11i1.39358.